Water Saving for Paddy Cultivation Under the System of Rice Intensification (SRI) in Eastern Indonesia - Mohammad Hasan; Shuichi Sato (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2007)
The System of Rice Intensification (SRI) developed in Madagascar in 1980s is a revolutionary new idea for paddycultivation to increase yields with reduced external resources. Basic idea of SRI originally proposed (Basic SRI) is to applycombination of (a) transplanting of young seedlings with wider spacing and (b) intermittent irrigation during vegetativegrowth period Further, application of organic fertilizers without use chemicals has practiced as